2010
DOI: 10.1126/science.1192148
|View full text |Cite
|
Sign up to set email alerts
|

Highly Silicic Compositions on the Moon

Abstract: Using data from the Diviner Lunar Radiometer Experiment, we show that four regions of the Moon previously described as "red spots" exhibit mid-infrared spectra best explained by quartz, silica-rich glass, or alkali feldspar. These lithologies are consistent with evolved rocks similar to lunar granites in the Apollo samples. The spectral character of these spots is distinct from surrounding mare and highlands material and from regions composed of pure plagioclase feldspar. The variety of landforms associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
173
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 188 publications
(181 citation statements)
references
References 27 publications
6
173
1
1
Order By: Relevance
“…[3] Recent results from the Diviner Lunar Radiometer Experiment on board the Lunar Reconnaissance Orbiter have shown that some other dome-shaped features on the Moon exhibit infrared spectra consistent with highly silicic compositions [Glotch et al, 2010;Greenhagen et al, 2010;Jolliff et al, 2011]. These features, which include the Gruithuisen domes, Hansteen alpha, and the Compton Bel'kovich anomaly, also exhibit strong Th anomalies in Lunar Prospector (LP) Gamma Ray Spectrometer (GRS) data, suggesting that they formed from highly evolved magmas [Lawrence et al, , 2005Hagerty et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…[3] Recent results from the Diviner Lunar Radiometer Experiment on board the Lunar Reconnaissance Orbiter have shown that some other dome-shaped features on the Moon exhibit infrared spectra consistent with highly silicic compositions [Glotch et al, 2010;Greenhagen et al, 2010;Jolliff et al, 2011]. These features, which include the Gruithuisen domes, Hansteen alpha, and the Compton Bel'kovich anomaly, also exhibit strong Th anomalies in Lunar Prospector (LP) Gamma Ray Spectrometer (GRS) data, suggesting that they formed from highly evolved magmas [Lawrence et al, , 2005Hagerty et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…This result, in addition to the relative lack of thermophysical anomalies at the swirl sites, strongly supports the solar wind standoff model and disqualifies the micrometeoroid/ comet swarm and dust levitation models for swirl formation. Diviner data can be used to determine the composition and degree of space weathering of the lunar surface 17,19,20 and to determine thermophysical properties using daytime and night-time thermal infrared measurements 21,22 . The ability to characterize both the compositional and thermophysical properties of the lunar regolith make Diviner well suited to examine the swirls and differentiate between the three proposed formation mechanisms.…”
mentioning
confidence: 99%
“…Remote sensing studies of several lunar domes show that they have high SiO 2 , low FeO, and high Th abundances (e.g., Wilson and Head 2003;Hagerty et al 2006;Glotch et al 2010Glotch et al , 2011, consistent with the compositions of silicic lithologies found in the lunar sample suite (e.g., Papike et al 1998). The most recent results from the Diviner Lunar Radiometer Experiment on the LRO have confirmed the presence of highly silicic volcanic domes on the Moon, thus supporting the strong correlation between silica-rich lithologies and elevated Th abundances (e.g., Hagerty et al 2006;Glotch et al 2010Glotch et al , 2011.…”
Section: Compositionmentioning
confidence: 77%
“…The most recent results from the Diviner Lunar Radiometer Experiment on the LRO have confirmed the presence of highly silicic volcanic domes on the Moon, thus supporting the strong correlation between silica-rich lithologies and elevated Th abundances (e.g., Hagerty et al 2006;Glotch et al 2010Glotch et al , 2011.…”
Section: Compositionmentioning
confidence: 78%